IMPLEMENTASI PEMBELAJARAN BERBASIS DEEP LEARNING DI LINGKUNGAN MADRASAH DALAM MEMBENTUK KARAKTER MULTIKULTURAL PADA MATA PELAJARAN AQIDAH AKHLAQ DI MTS AL MA’RUF DENPASAR BALI - Umroh; Arjiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of deep learning-based Islamic Theology and Ethics (Akidah Akhlak) instruction in shaping multicultural character among students at MTs Al Ma’ruf Denpasar, Bali. A descriptive qualitative approach was employed, utilizing data collection techniques including classroom observation, in-depth interviews, and document analysis. The findings reveal that instructional planning was contextually designed to emphasize the internalization of universal Islamic values such as tolerance, justice, and compassion within a pluralistic society. The learning process was participatory and reflective, involving open discussions, moral journals, and ethical social projects. Evaluation was conducted through authentic and character-oriented assessments, utilizing narrative instruments and social attitude rubrics. This study concludes that deep learning approaches in Islamic education offer an effective model for developing students’ awareness of diversity grounded in Islamic ethical values. The contribution of this research lies in proposing an integrative and transformative pedagogical framework applicable to Islamic education in multicultural settings.